2020
DOI: 10.1177/0956247820907808
|View full text |Cite
|
Sign up to set email alerts
|

Getting urban density to work in informal settlements in Africa

Abstract: The drawbacks of crowded informal settlements stand in stark contrast to the theoretical promise that urban density is the key to building more productive, sustainable and resilient cities. African cities cannot be expected to prosper while the majority of residents live in sprawling informal settlements with no prospect of improvement beyond the provision of basic services. There is a strong case for governments to embrace a broader reconstruction agenda in order to harness the potential of density for all-ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…cities into slums and central business districts to spatially allocate plastic emissions of HCl, as the use of plastic is concentrated in low-cost and informal settlements. This then accounts for the distribution of informal settlements within cities, as is the case for many cities in Africa (World Bank, 2016;Visagie et al, 2020). This spatial allocation is limited to plastic emissions of HCl only, which are relatively minor in comparison to the other activities.…”
Section: Estimating Emissions From the Charcoal Industry In Africamentioning
confidence: 99%
“…cities into slums and central business districts to spatially allocate plastic emissions of HCl, as the use of plastic is concentrated in low-cost and informal settlements. This then accounts for the distribution of informal settlements within cities, as is the case for many cities in Africa (World Bank, 2016;Visagie et al, 2020). This spatial allocation is limited to plastic emissions of HCl only, which are relatively minor in comparison to the other activities.…”
Section: Estimating Emissions From the Charcoal Industry In Africamentioning
confidence: 99%
“…The household survey data and the outcomes of the quantitative analysis highlight that areas with high urban densities also have greater proportions of tenants, more overcrowding, and lower levels of access to water and sanitation. However, the relation between property prices, location, and urban density of informal settlements in Sub-Saharan Africa remains under-researched [37]. Accordingly, further studies are needed to validate the hypotheses formulated in this paper.…”
Section: Discussionmentioning
confidence: 90%
“…But higher population densities may not translate into well-being. Yet, research has demonstrated that densification in Global South cities can produce creative productivity and prosperity (see Bardhan et al 2015b, Brown 2017, Kshetrimayum et al 2020, Visagie & Turok 2020. A prominent characteristic of Southern cities is the concentration of population in informal settlements.…”
Section: Literature Reviewmentioning
confidence: 99%